Parametric Modelling for Designing Offsite Construction. (2017) - Sharma, Shrutiniwas; Sawhney, Anil; Arif, Mohammed
Abstract: Increasing population and progressing economies around the world are generating huge demand for built assets. When this demand is dealt with conventional 'sticks-and-bricks' approach, it leads to usual delays, wastages, cost overruns, and quality issues, etc. Consequently, the traditional approach results in negative impacts on economic and social scenarios apart from being just unable to deliver required supply level of built assets. On the other hand, offsite construction techniques, when utilized appropriately, can significantly speed up the construction process and improve the quality of deliverables in addition to bringing in improved sustainability and better worker health and safety. But offsite practices are marred with a general perspective of its being cause of rigidity in the design processes and disproportional increment in coordination requirements. To address this perceived problem, the application of Building Information Modelling (BIM) has been conceptualized for the design of a prototype in this research. Simpler ways of modularization and effective optimization of design through parametric modelling has been developed. The methodology coming out of this design exercise, which is of reporting values of parametric variables real-time, is promising in the sense of ensuring the general and flexible usage of offsite practices. Further as experienced during the BIM modelling exercise for the prototype, the design iterations can be accomplished in a more informed manner and optimization run in an automated fashion by using the Application Programming Interface (API) of BIM authoring tool by taking advantage of already defined key parameters. This paper addresses these important issues at the conceptual level and determines a roadmap for further research.